The State Responsibilities Relating to Human Rights Violations to The People with Stateless Persons Status in Rohingnya Crisis - I Putu Dwika Ariestu (Jurnal Magister Hukum Udayana, 2018)
Human Rights and the State could not be separated from one another. Both are interconnected in terms of how to ensure internal stability in a country. With the existence of human rights, it is hoped that state is not arbitrary to treat its people and is obliged to protect everyone in its territory including in this case Stateless persons mentioned in Article 7 paragraph 1 of the Convention relating Status of Stateless Persons in 1954. This study aims to analyze the obligations the State must take in relation to the protection of persons with stateless persons status, and to recognize the legal consequences and responsibilities of States in the event of omitting acts of human rights violations against people with stateless persons status. This paper using normative research methods with statute approach and conceptual approach. The study shows that in relation to the obligation of the state that each State shall be obliged to provide protection to persons with stateless persons status as stipulated in the 1954 Convention and the provisions of the International Human Rights Law, the obligations of state protection include the protection of the right to life, the right to employment and even the right to obtain citizenship status. The international legal consequences accepted by the state are listed in Article 39, Article 41, and 42 of the UN Charter. Then for state responsibility are listed under Article 35, Article 36, and Article 37 of UNGA 56/83 of 2001.